COMPARATIVE PHYTOCHEMICAL AND BIOLOGICAL INVESTIGATION OF FIVE GLYCINE MAX (L.) MERRILL GENOTYPES - ABD-ALLA, HOWAIDA I; A. A TAIE, HANAN; ABD-ELMOTALEB, MARWA M (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Soybean (Glycine max L. Merrill) is the world’s most important consumed seed legume. The objectives of the present study were to determine the variability in phytochemical composition and biological activities between five genotypes of G. max. Methods: Lipoidal matters were determined using glucose (GLC). Amino acids were detected by the amino acid analyzer. The phytoconstituents present within each ethanol extract was investigated by gas chromatography-mass spectrometry. The amount of total phenolics, flavonoids, and tannins was analyzed using a spectrophotometric technique, based on Folin–Ciocalteu reagent, aluminum chloride colorimetric assay, and the modified vanillin hydrochloric acid method, respectively. Quercetin, catechin, and gallic acid were used as standard compounds, respectively. Isoflavones content were detected by high-performance liquid chromatography (HPLC)/photodiode array (PDA). The radical scavenging and antioxidant capacity of the genotypes using different in vitro analytical assays such as 2,2-diphenyl,1-picryl hydrazyl, 2,2’-Azino-bis(3-ethylbenzothiazoline-6-sulphonic acid, reducing power, metal chelating, and ferric reducing anti-oxidant power. Butyl hydroxyl toluene and trolox were used as the reference antioxidant radical scavenger compounds. Antitumor activity was evaluated by detecting the viability of Ehrlich ascites carcinoma cells on four different concentrations (1–5 mg/mL). Results: GLC analysis showed the high value of total unsaturated fatty acids and 16 amino acids including glutamic acid with the highest concentration. The variation between genotypes according to their chemical composition of the aldehydes, esters, ketones, alcoholics, and carboxylic content were reported. HPLC/PDA referred to the presence of daidzein, genistein, and in all genotypes. Conclusion: The results confirm the higher value of phytoconstituents of the genotype Giza 35 and Giza 21 as well as their better bioactivity.